Google Scholar Retrieves Twice as Many Relevant Citations as PubMed and Provides Greater Full-Text Access for Quick, Clinical Nephrology Searches - Diana K. Wakimoto (Evidence Based Library and Information Practice, 2014)
Objective – To compare recall and precision of results retrieved by searches in PubMed and Google Scholar for clinical nephrology literature.